Impact of Covid-19 on the future of rural migration in Bangladesh - CGIAR Research Program on Water, Land and Ecosystems (2021)
The phone survey was completed in 11/2021 and no research papers are available but we shared preliminary results at a steering committee meeting - https://www.slideshare.net/ifpri/gendersensitive-risks-and-options-assessment-for-decision-making-road-to-support-wif2-250923168